Occurrence of a huntsman spider Olios lamarcki Latreille, 1806 (Araneae: Araneomorphae: Sparassidae) from Nijhum dwip, Bangladesh (Bangladesh Journal of Zoology, 2017)
Abstract not availableBangladesh J. Zool. 45(1): 97-100, 2017